Neurospora Bibliography - Craig Wilson (Fungal Genetics Reports, 2004)
This bibliography represents my attempt to collect all works dealing substantially with Neurospora. Please let me know of anything published in 2002 or 2003 that is not included here or in the previous bibliography, so that it might be mentioned next year. I would be especially happy to hear of chapters from books, and articles from journals not indexed in major bibliographic services. Please also let me know of any errors in citation. Please send reprints or copies of articles to the Fungal Genetics Stock Center.